MOLECULAR GENETIC ANALYSIS OF INFECTION AGENTS OF FARM ANIMALS ANAPLASMOSIS ON THE TERRITORY OF WESTERN AND EASTERN SIBERIA - V. A. Par (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
A total of 452 blood samples of cattle, sheep and goat collected in different regions of Altai Republic, Altai region, Novosibirsk and Irkutsk regions were examined on the presence of Anaplasma DNA using nested PCR with subsequent sequencing of PCR fragments. Anaplasma DNA was found in all examined blood samples of goat, 75.2 % samples of sheep, and 49.3 % samples of cattle. A molecular genetic analysis has demonstrated that intraerythrocytic Anaplasma ovis circulates in goat and sheep blood, while an intraerythrocytic Anaplasma sp. Omsk and a new intraerythrocytic Anaplasma sp. Sibl22, which cannot be attributed to any known species, circulate in cattle blood. In addition to intraerythrocytic Anaplasma, DNA of monocytic Anaplasma bovis was found in one blood sample of cattle.